The Casting or the Two-Headed Spectator – a give and take process – - ALDEA, Diana (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
This paper analyses the process of casting in theatre, by focusing on the actor-director information exchanges. The author starts from the premise that a casting session is, essentially, a theatrical situation with two players who alternate their roles.